Morphological Variation of Limnonectes blythii in West Sumatera, Indonesia: - (International Journal of Scientific Research and Management (IJSRM), 2018)
Abstract: This study aimed to analyze the morphological variations of Limnonectes blythii in West Sumatra by using morphometric in Genetics and Cytology Laboratory, Department of Biology, Faculty of Mathematics and Natural Sciences, Andalas University, Padang. The sample of this research was collected directly in West Pasaman (Nature Reserves Malampah), Sijunjung (Nature Reserve Pangean) and Payakumbuh (Harau Nature Reserve) in February until Mai 2015. The results showed that there is genetic variation in morphology of the population L. blythii in Malampah and Pangean as the first cluster with a population in Harau. The kinship between populations in Pangean and Malampah as the second cluster is closer to the population at second subcluster with Harau population and have the more distant kinship of the population L. blythii in Pangean. It was concluded that 12 morphological characters show differentiation significant (p≥ 0005) of the population, while the population of Harau and Sijunjung showed significant differentiation as many as 10 characters (32.2%), Between population differentiation Harau with Malampah show as much as 8 characters (25.8% ), and between population Malampah with Sijunjung show 7 (22:58%) differentiated character. This study requires molecular analysis to clarify the phylogenetic relationships among L. blythii to preserve the information of this frog as an export commodity.